Biocontrol of postharvest fungal decay of tomatoes with a combination of thymol and salicylic acid screening from 11 natural agents. (October 2016) - Kong, Jie; Xie, Yun-Fei; Guo, Ya-Hui; Cheng, Yu-Liang; Qian, He; Yao, Wei-Rong
Abstract: To control the decay of fresh vegetables or fruits after harvest and overcome higher costs using a natural agent, synergistic antifungal effects were studied in tomatoes and their main decay fungi Fusarium solani and Rhizopus stolonifer. After screening 56 groups with a checkerboard method based on 11 natural agents, only one combination of thymol and salicylic acid (STSA ) had a synergistic effect on both fungi. Their average minimal inhibitory concentration (MIC) values decreased significantly to 0.43 fold compared with the single agents tested. Their mycelial growth was completely inhibited; the inhibition rates of spore germination exceeded 96% at 0.5, 1, and 2 MIC. The protective and therapeutic effects were found to be dose-dependent during exposure; the former was always better than the latter against both fungi at any tested concentration in wound-inoculated tomatoes, and phytotoxicity occurred only when the concentration of STSA reached 2 MIC in naturally stored fruit. Consumer evaluation showed that the natural, non-inoculated tomatoes treated with 1 MIC and the wound-inoculated tomatoes treated with 2 MIC were both acceptable. The in vitro and in vivo results show that a combination of thymol and salicylic acid could be developed as a control measure and could reduce costs. Highlights: The combination of thymol and salicylic acid had a synergistic effect on both fungi. STSA effectively inhibited spore germination and mycelial growth. Exposure to STSA showed protective and therapeutic effects in a dose-dependent manner. Sensory evaluation showed practical efficacy of STSA as fungistat in tomatoes.